2006
DOI: 10.1128/jvi.80.8.3893-3903.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Mutants of JC Virus Agnoprotein Are Unable To Sustain the Viral Infection Cycle

Abstract: Many eukaryotic and viral regulatory proteins are known to undergo posttranslational modifications including phosphorylation, which plays a critical role in many aspects of cell function. Previous studies from our and other laboratories indicated that the JC virus (JCV) late regulatory protein, agnoprotein, plays an important role in the JCV life cycle. Agnoprotein contains several potential phosphorylation sites, including Ser7, Ser11, and Thr21, which are potential targets for the serine/threonine-specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 46 publications
6
87
0
Order By: Relevance
“…For instance, our recent protein-protein interaction studies with agnoprotein and LT-Ag showed that agnoprotein stimulates LT-Ag binding to the viral origin of replication (Ori), through which it contributes to the viral replication cycle (4). We have also previously reported that alterations in the protein kinase C (PKC) phosphorylation sites of JCV agnoprotein (conversion of Ser7, Ser11, and Thr21 to Ala) resulted in phenotypes that are unable to sustain the viral replication cycle (19). Deletion of either the intrinsically disordered Cterminal region (the sequence from amino acids 51 to 71) (2,79) or internal sequences containing the ␣-helix region (amino acids 17 to 42) (7) resulted in a replication-incompetent virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, our recent protein-protein interaction studies with agnoprotein and LT-Ag showed that agnoprotein stimulates LT-Ag binding to the viral origin of replication (Ori), through which it contributes to the viral replication cycle (4). We have also previously reported that alterations in the protein kinase C (PKC) phosphorylation sites of JCV agnoprotein (conversion of Ser7, Ser11, and Thr21 to Ala) resulted in phenotypes that are unable to sustain the viral replication cycle (19). Deletion of either the intrinsically disordered Cterminal region (the sequence from amino acids 51 to 71) (2,79) or internal sequences containing the ␣-helix region (amino acids 17 to 42) (7) resulted in a replication-incompetent virus.…”
Section: Discussionmentioning
confidence: 99%
“…JCV agnoprotein was previously shown to interact with a number of cellular and viral proteins, including YB-1 (11), p53 (12), FEZ1 and HP1-␣ (13), adaptor protein complex 3 (14), JCV small t antigen (Sm t-Ag) (15), and JCV large T antigen (LT-Ag) (16), and has been implicated in various aspects of the JCV life cycle, including viral replication (4,17), viral transcription (11), functioning as a viroporin (14,18), encapsidation (19), and interfering with exocytosis (20). In addition, this protein deregulates cell cycle progression, where cells stably expressing agnoprotein largely accumulate at the G 2 /M phase of the cell cycle (12).…”
mentioning
confidence: 99%
“…Agnoprotein can be phosphorylated by protein kinase C, and several potential sites including serine at positions 7 and 11 have been implicated experimentally (54,62). Here, we altered serine 7 and serine 11 to alanine and serine 15 to valine by site-directed mutagenesis and developed CG-4 cells that can constitutively express the mutant protein.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo kinase assays demonstrated that agnoprotein is a target for phosphorylation by PKC. When each of the PKC phosphorylation sites was mutated to Ala singly and in combination, virus containing each of these mutations failed to propagate (104). Thus, phosphorylated forms of agnoprotein may have essential functions in the viral life cycle.…”
Section: Recent Studies Of Primate Polyomavirusesmentioning
confidence: 99%